(Electro)chemical Oxidation of 6, 13‐Bis[tri(isopropyl)silylethynyl]pentacene to its Radical Cation and Dication1. Issue 16 (20th July 2017) - Schundelmeier, Simon; Speiser, Bernd; Bettinger, Holger F.; Einholz, Ralf
Abstract: 6, 13‐Bis[tri(isopropyl)silylethynyl]pentacene is a prototypical molecule for organic semiconductor and photovoltaic materials, which makes its electrochemical (redox) properties highly interesting. However, previous cyclic voltammetric studies have provided only limited information. Kinetic and persistence information and identification of the oxidation product(s) and their further reaction or oxidation have not been reported. Thus, an extended electrochemical and spectroscopic investigation of this compound was conducted in CH2 Cl2 and THF electrolytes at Pt electrodes. The electrochemically and chemically generated radical cation of the title compound was characterized by using ESR and UV/Vis/NIR spectroscopy and quantum‐chemical modeling. In CH2 Cl2, further oxidation to a dication with chemical reversibility at fast timescales but follow‐up reactivity at slow timescales was observed. Pertinent parameters of the electron transfers (formal potentials E 0, electron transfer rate constants k s, electron stoichiometry n ) were determined. The diffusion coefficients, D, in the two electrolytes were estimated from electrochemical and pulse gradient spin echo (PGSE) NMR spectroscopy data. Simulations of cyclic voltammograms supported the proposed oxidation mechanism and allowed the estimation of further reaction parameters. Abstract : One‐electron oxidation : A detailed electrochemical study of 6, 13‐bis[tri(isopropyl)silylethynyl]pentacene (TIPS‐pentacene) reveals the characteristics of the one‐electron oxidation of this acene, which is famous for its applications in organic electronics, and the formation of a reactive dication at more positive potentials.